Chemotactic signalling in Rhodobacter sphaeroides requires metabolism of attractants. - Poole, P S (1993)
Rhodobacter sphaeroides showed chemotaxis towards L-alanine but not towards the analog 2-aminoisobutyrate. 2-Aminoisobutyrate and alanine were shown to share a common transport system, but 2-aminoisobutyrate was not metabolized. Chemotaxis towards alanine was inhibited by structurally unrelated metabolites, suggesting cross-inhibition by common metabolic intermediates.